KONDISI TERUMBU KARANG DAN ASOSIASINYA DENGAN BINTANG LAUT DI PERAIRAN PULAU TUNDA, KABUPATEN SERAM, PROVINSI BANTEN - Zamani, Neviaty P (Jurnal Teknologi Perikanan dan Kelautan, 2016)
Coral reef constitute extremely uniquely ecosystem with various of life forms. A lot of sea star Linckia laevigata werefound to associate with coral reef in Tunda Island, Serang Regency, Banten. This research was conducted on January-February 2014 that located in Tunda Island, Serang Regency, Banten. Determination of observatory station was usingtime swimming (snorkeling) with observing the existence of coral reef and sea star that associated with coral reef.Assessment of coral reef condition was determined by Line Intercept Transect method and abundance of sea stardetermined by belt transect method. The parameter of water quality were found in entire sites of sampling were stillappropriated with coral reef life and sea star. The result showed that coral cover were between 54.95-73.00%. Life form was dominated by massive and foliose coral. Abundance of Linckia laevigata that found in Tunda Island water was 8-45 ind/100 m2. This association occurred between coral reef and Linckia laevigata that constitute association of the mutualistic symbiosis.